Development Study and Effectiveness of Online Data Based Scientific Writing Model Using Endnote Application for MGMP Chemistry Teachers Padang Panjang City - Rahadian Zainul; Budhi Oktavia; Edi Nasra; Visca Alisia Arianti; Putri Fatimah; Yulia Mona Liza; Trihanto Setiadi (Fakultas MIPA Universitas Negeri Padang, 2019)
In writing scientific work, a work system is needed online (online) so that the search process is fast and accurate. The online data-based writing model with endnote application is an alternative model of scientific writing that can be applied to school teacher teachers and lecturers. The purpose of this study was to develop a model of scientific writing and measure the effectiveness of its application to MGMP Chemistry teachers in Padang Panjang City. The method used is the development of the ADDIE model and the success test with CV (Coefficient of Variations). Implementation is carried out on all Chemistry teacher teachers who are members of the Padangpanjang City Chemical MGMP. Each teacher will receive training and assistance in creating an Online Library as a database. The training continued with the application of the preparation of scientific works based on student learning outcomes data in each school. From the results of the study, it was found that the level of ease in literacy and compilation of scientific work reached 70% SS and 30% S. The level of interest of Master in compiling scientific work with Endnote reached 30%. SS san 70% S. The desire of participants to start compiling scientific work reaches 20% US, 60% S and 20% SS. The training effectiveness test found that the coefficient of variation had decreased from 2.75% to 1.63%, so it could be concluded that the model for the preparation of scientific work was successfully applied to the Teachers of the Padangpanjang Chemical MGMP.